The state of the art in therapeutic administration of botulinum toxin in children with cerebral palsy: an integrative review - Sandro Rachevsky Dorf; Adriana Rodrigues Fonseca; Flávio Roberto Sztajnbok; Thiffany Rodrigues Delfino de Oliveira; Linamara Rizzo Basttistella (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To describe the current state of the art in the therapeutic administration of botulinum toxin with indications, efficacy, and safety profile for children and adolescents with cerebral palsy. Data source: An integrative review was conducted. The MEDLINE/PubMed database was searched twice within the last decade using distinct terms, and only studies written in the English language were included. The study population was limited to those aged 0-18 years. Articles that were duplicates or lacked sufficient methodology information were excluded. Data synthesis: We found 256 articles, of which 105 were included. Among the included studies, most were conducted in developed countries. Botulinum toxin demonstrated good safety and efficacy in reducing spasticity, particularly when administered by a multidisciplinary rehabilitation team. It is primarily utilized to improve gait and upper limb function, facilitate hygiene care, reduce pain, prevent musculoskeletal deformities, and even decrease sialorrhea in patients without a functional prognosis for walking. Conclusions: The administration of botulinum toxin is safe and efficacious, especially when combined with a multi-professional rehabilitation team approach, which increases the probability of functional improvement. It can also be beneficial for patients with significant functional impairments to help with daily care tasks, such as hygiene, dressing, and reducing sialorrhea. Pediatricians must be familiar with this treatment and its indications to attend to and refer patients promptly when necessary, and to exploit their neuroplasticity. Further research on this topic is required in developing countries.